The mythic species Issus analis Brullé, 1833 (Hemiptera, Fulgoroidea, Issidae): still an enigmatic taxon - Gnezdilov, Vladimir M.; Bourgoin, Thierry (Zootaxa, 2017)
One Issidae specimen stored in Paris museum historical collections is reported as holotype of Issus analis Brullé, 1833. From the original description, which is confirmed by study of this specimen, the species is moved to the genus Zopherisca Emeljanov, 2001 under a new combination Zopherisca analis (Brullé, 1833), comb. n. Date of description is discussed and modified from 1832 to 1833 accordingly. Unfortunately being a female as type specimen, the species remains quite enigmatic until some molecular analsysis could be undertaken on this old material.